When A New Product Innovatıon Negatıvely Impacts Marketıng Performance - I Gusti Agung Teja Kusuma; Gregorius Paulus Tahu; Anak Agung Dwi Widyani; Murtini Langgeng (APMBA (Asia Pacific Management and Business Application), 2022)
This study analysed the influence of market orientation and product innovation capability on product competitiveness to improve marketing performance on clay handicraft products in Bali-Indonesia during the Covid-19 pandemic. New insights were offered to the research subjects of clay craftsmen, and in previous studies this type of sample was rarely considered. We studied the relationships of all the variables involved. Empirical evidence was conveyed through a survey involving 60 SMEs as a saturated sample, using a PLS-based SEM as analysis tool. The results show that all direct relationships of variables are proven to be significantly positive, except that product innovation capability has a significant negative impact on marketing performance. The character of the clay craft industry has a uniqueness that was not previously thought of. The greater the ability to produce new innovation seems to have an unfavourable impact on sales of previous innovations. The unique characteristics of the industry disturbed by the Covid-19 situation adds to the narrowness of the market. A market expansion strategy is needed by developing the character of the product from pure artistic nature to decorative decoration into a combination with functionality. To achieve this goal, it is apparently constrained by the limited demographic characteristics and competence of SMEs to innovate. Originality/value; analysing innovation based on three characteristics, namely artistic, symbolic and functional, as an important variable in the clay industry in relation to consumer behaviour. The three proposed analysis based on the characteristics of product innovation had never been studied in previous studies